Li Ion Diffusivity and Rate Performance of the LiFePO4 Modified by Cr Doping - Park, Chang Kyoo; Park, Sung Bin; Shin, Ho Chul; Cho, Won Il; Jang, Ho (WILEY-V C H VERLAG GMBH, 2011)
This study reports the root cause of the improved rate performance of LiFePO4 after Cr doping. By measuring the chemical diffusion coefficient of lithium (Du) using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), the correlation between the electrochemical performance of Li FePO4 and Li diffusion is acquired. The diffusion constants for LiFePO4/C and LiFe0.97Cr0.03PO4/C measured from CV are 2.48 x 10(-15) and 4.02 x 10(-15) cm(2) s(-1), respectively, indicating significant increases in diffusivity after the modification. The difference in diffusivity is also confirmed by EIS and the Du values obtained as a function of the lithium content in the cathode. These results suggest that Cr doping facilitates Li ion diffusion during the charge-discharge cycles. The low diffusivity of the LiFePO4/C leads to the considerable capacity decline at high discharge rates, while high diffusivity of the LiFe0.97Cr0.03PO4/C maintains the initial capacity, even at high C-rates.